Effects of person-centered care on residents and staff in aged-care facilities: a systematic review - Brownie, Sonya; Nancarrow, Susan (Clinical interventions in aging, 2013)
Several residential aged-care facilities have replaced the institutional model of care to one that accepts person-centered care as the guiding standard of practice. This culture change is impacting the provision of aged-care services around the world. This systematic review evaluates the evidence for an impact of person-centered interventions on aged-care residents and nursing staff. We searched Medline, Cinahl, Academic Search Premier, Scopus, Proquest, and Expanded Academic ASAP databases for studies published between January 1995 and October 2012, using subject headings and free-text search terms (in UK and US English spelling) including person-centered care, patient-centered care, resident-oriented care, Eden Alternative, Green House model, Wellspring model, long-term care, and nursing homes. The search identified 323 potentially relevant articles. Once duplicates were removed, 146 were screened for inclusion in this review; 21 were assessed for methodological quality, resulting in nine articles (seven studies) that met our inclusion criteria. There was only one randomized, controlled trial. The majority of studies were quasi-experimental pre-post test designs, with a control group (n = 4). The studies in this review incorporated a range of different outcome measures (ie, dependent variables) to evaluate the impact of person-centered interventions on aged-care residents and staff. One person-centered intervention, ie, the Eden Alternative, was associated with significant improvements in residents' levels of boredom and helplessness. In contrast, facility-specific person-centered interventions were found to impact nurses' sense of job satisfaction and their capacity to meet the individual needs of residents in a positive way. Two studies found that person-centered care was actually associated with an increased risk of falls. The findings from this review need to be interpreted cautiously due to limitations in study designs and the potential for confounding bias. Typically, person-centered interventions are multifactorial, comprising: elements of environmental enhancement; opportunities for social stimulation and interaction; leadership and management changes; staffing models focused on staff empowerment; and assigning residents to the same care staff and an individualized philosophy of care. The complexity of the interventions and range of outcomes examined makes it difficult to form accurate conclusions about the impact of person-centered care interventions adopted and implemented in aged-care facilities. The few negative consequences of the introduction of person-centered care models suggest that the introduction of person-centered care is not always incorporated within a wider "hierarchy of needs" structure, where safety and physiological need are met before moving onto higher level needs. Further research is necessary to establish the effectiveness of these elements of person-centered care, either singly or in combination.